Composite sintered body and manufacturing method thereof
Patent Information
- Application Number
- JP2024225110
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2039-10-30
AI Technical Summary
【0022】 本発明では、電極の抵抗率の増大を抑制しつつ、電極と基材との熱膨張係数の差を小さくすることができる。
Smart Images

Figure 2025028348000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a compound sintered body and a method for producing the compound sintered body. [Background technology]
[0002] Conventionally, in semiconductor substrate manufacturing equipment and the like, susceptors such as electrostatic chucks that attract and hold semiconductor substrates, heaters that heat semiconductor substrates, and electrostatic chuck heaters that combine these have been used. The susceptor includes a base material whose main material is a sintered ceramic (e.g., aluminum nitride) and an electrode disposed inside the base material.
[0003] In the above-mentioned manufacturing apparatus, a process such as film formation or etching is performed on a semiconductor substrate supported by a susceptor using plasma generated by exciting a processing gas. In the susceptor, an additive such as magnesium oxide may be added to the substrate for the purpose of maintaining the volume resistivity at high temperatures in order to cope with the high temperatures of the above-mentioned processes. Since the thermal expansion coefficient of the substrate varies depending on the type and addition rate of the additive, there is a possibility that cracks or breakage may occur in the substrate due to the difference in the thermal expansion coefficient between the substrate and the electrode.
[0004] Therefore, Patent Document 1 proposes that in a heating resistor embedded in a base made of an aluminum nitride sintered body, the difference in thermal expansion coefficient between the base and the heating resistor is reduced by mixing 90% by weight to 99% by weight of tungsten, molybdenum, tungsten carbide, titanium carbide or titanium nitride with 1% by weight of aluminum nitride (i.e., the material of the base).
[0005] Furthermore, Patent Document 2 proposes that in an electrode embedded in a ceramic substrate such as aluminum nitride, aluminum oxide, or yttrium oxide, the difference in thermal expansion coefficient between the substrate and the electrode be reduced by mixing 5% by weight to 30% by weight of the material of the ceramic substrate with a high-melting point metal such as tungsten or molybdenum.
[0006] On the other hand, Patent Document 3 proposes a bipolar electrostatic chuck in which the attraction electrodes embedded in a ceramic dielectric layer made of aluminum nitride are formed from a sintered body of molybdenum, tungsten, titanium, titanium nitride, tungsten carbide, or titanium carbide. In this electrostatic chuck, the thickness of each portion of the ceramic dielectric layer is specified, so that the wafer is uniformly fixed on the attraction surface. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 8-236599 [Patent Document 2] Patent No. 5032444 [Patent Document 3] JP 2007-173592 A Summary of the Invention [Problem to be solved by the invention]
[0008] In Patent Documents 1 and 2, the difference in thermal expansion coefficient between the substrate and the electrode can be reduced to a certain extent by adding the substrate material to the electrode, but there is a limit to how much the difference can be reduced. In addition, adding the substrate material to the electrode may increase the resistivity of the electrode, which may reduce the amount of heat generated.
[0009] In the electrostatic chuck of Patent Document 3, no consideration is given to reducing the difference in thermal expansion coefficient between the ceramic dielectric layer and the chucking electrode to suppress cracks and breakages in the ceramic dielectric layer. In addition, in the electrostatic chuck, when the electrode is formed from molybdenum, tungsten, or titanium, it is easily affected by the sintering conditions and the base material, and oxidation and carbonization occur, making the inside of the electrode uneven. As a result, the electrode characteristics are likely to vary, and mass productivity may decrease. On the other hand, when the electrode is formed from titanium nitride, high-temperature sintering during the manufacture of the electrostatic chuck may cause abnormal grain growth of titanium nitride, resulting in voids between the particles, and the resistivity of the electrode may increase.
[0010] The present invention is directed to a composite sintered body, and has an object to reduce the difference in thermal expansion coefficient between the electrode and the substrate while suppressing an increase in the resistivity of the electrode. [Means for solving the problem]
[0011] A composite sintered body according to a preferred embodiment of the present invention includes a disk-shaped base material containing 5% by mass to 45% by mass of magnesium aluminum spinel with the remainder being aluminum nitride, on whose main surface a semiconductor substrate is placed, and an electrode disposed inside or on the surface of the base material. The electrode contains tungsten carbide (WC) and titanium nitride (TiN). This makes it possible to reduce the difference in thermal expansion coefficient between the electrode and the base material while suppressing an increase in the resistivity of the electrode.
[0012] Preferably, the total content of the tungsten carbide (WC) and the titanium nitride (TiN) in the conductor contained in the electrode is 100% by volume.
[0013] A compound sintered body according to another preferred embodiment of the present invention includes a disk-shaped base material containing 50 mass % to 100 mass % aluminum nitride and having a semiconductor substrate placed on a main surface thereof, and an electrode disposed inside or on the surface of the base material. The electrode contains tungsten carbide (WC) and titanium nitride (TiN). The total content of the tungsten carbide (WC) and the titanium nitride (TiN) in the conductor contained in the electrode is 100 volume %. This makes it possible to reduce the difference in thermal expansion coefficient between the electrode and the base material while suppressing an increase in the resistivity of the electrode.
[0014] Preferably, the total content of said tungsten carbide (WC) and said titanium nitride (TiN) in said electrode is 100% by volume.
[0015] Preferably, the resistivity of the electrode at room temperature is 3.0×10 -5 Ω·cm or less.
[0016] Preferably, the content of titanium nitride (TiN) in the conductor contained in the electrode is 5 volume % or more and 60 volume % or less.
[0017] Preferably, in the electrode, the intensity ratio of the main peak of the tungsten carbide (WC) to the main peak of the titanium nitride (TiN) obtained by X-ray diffraction is not less than 0.80 and less than 1.0.
[0018] Preferably, the sintered grain size of the titanium nitride (TiN) in the electrode is 0.7 μm or more and 1.0 μm or less.
[0019] The present invention is also directed to a method for manufacturing a compound sintered body comprising a disk-shaped base material on whose main surface a semiconductor substrate is placed and an electrode disposed inside the base material. A method for manufacturing a compound sintered body according to a preferred embodiment of the present invention comprises the steps of: a) preparing a first member and a second member which are a compact, a calcined body or a sintered body mainly made of ceramic; b) arranging an electrode or a precursor of the electrode containing tungsten carbide (WC) and titanium nitride (TiN) on the first member, and then stacking the second member to form a laminate; and c) hot-pressing and firing the laminate. The first member and the second member after the step c) contain 5% to 45% by mass of magnesium aluminum spinel and the remainder is aluminum nitride. This makes it possible to reduce the difference in thermal expansion coefficient between the electrode and the base material while suppressing an increase in the resistivity of the electrode.
[0020] A method for producing a composite sintered body according to another preferred embodiment of the present invention includes the steps of: a) preparing a first member and a second member, which are a compact, a calcined body, or a sintered body mainly made of ceramic; b) disposing an electrode or a precursor of the electrode containing tungsten carbide (WC) and titanium nitride (TiN) on the first member, and then stacking the second member to form a laminate; and c) hot-pressing and firing the laminate. After the step c) is completed, the first member and the second member contain 50 mass % to 100 mass % of aluminum nitride. After the step c) is completed, the total content of the tungsten carbide and the titanium nitride in the conductor contained in the electrode is 100 volume %. This makes it possible to reduce the difference in thermal expansion coefficient between the electrode and the substrate while suppressing an increase in the resistivity of the electrode.
[0021] Preferably, the firing temperature in step c) is 1700°C or higher and 1780°C or lower. Effect of the Invention
[0022] In the present invention, it is possible to reduce the difference in thermal expansion coefficient between the electrode and the substrate while suppressing an increase in the resistivity of the electrode. [Brief description of the drawings]
[0023] [Figure 1] FIG. 2 is a cross-sectional view of a susceptor. [Diagram 2] FIG. 2 is a diagram showing a manufacturing flow of a compound sintered body. [Diagram 3] 1 is an SEM image of the polished surface of an electrode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] FIG. 1 is a cross-sectional view of a susceptor 1 according to one embodiment of the present invention. The susceptor 1 is a semiconductor manufacturing equipment component used in a semiconductor manufacturing equipment. The susceptor 1 supports a substantially disk-shaped semiconductor substrate 9 (hereinafter simply referred to as "substrate 9") from the lower side in FIG. 1. In the following description, the upper and lower sides in FIG. 1 will be simply referred to as the "upper side" and "lower side". Also, the up-down direction in FIG. 1 will be simply referred to as the "up-down direction". The up-down direction in FIG. 1 does not necessarily have to coincide with the actual up-down direction when the susceptor 1 is installed in the semiconductor manufacturing equipment.
[0025] The susceptor 1 includes a main body 21, a base 22, and an electrode 23. The main body 21 is a substantially plate-shaped (e.g., substantially disk-shaped) base material made mainly of ceramic. The substrate 9 is placed on the upper main surface (i.e., the upper surface) of the main body 21. The base 22 is a substantially plate-shaped (e.g., substantially disk-shaped) member larger than the main body 21 in a plan view. The main body 21 is attached on the base 22. In the example shown in FIG. 1, the electrode 23 is disposed (i.e., embedded) inside the main body 21. The electrode 23 is, for example, a substantially disk-shaped member. The electrode 23 is preferably formed of a material having a relatively high melting point. The main body 21 and the electrode 23 are a compound sintered body formed of a plurality of materials. In the following description, the main body 21 and the electrode 23 are also collectively referred to as the "compound sintered body 20". The materials of the main body 21 and the electrode 23 will be described later.
[0026] 1, the susceptor 1 is a heater that heats the substrate 9 with heat generated by applying a DC voltage to the electrode 23. That is, the electrode 23 is a resistance heating element that heats the substrate 9. In the susceptor 1, in addition to the electrode 23, a chuck electrode that electrostatically attracts the substrate 9 by utilizing Coulomb force or Johnsen-Rahbek force may be provided inside the main body 21. Alternatively, the electrode 23 may be used as the chuck electrode.
[0027] As described above, the main body 21 is formed with ceramic as the main material. In the main body 21, the content of the ceramic as the main material is, for example, 50% by mass to 100% by mass. The main material of the main body 21 is, for example, aluminum nitride (AlN). In the main body 21, an additive material such as magnesium oxide (MgO) and / or magnesium aluminum spinel (MgAl2O4) may be added to AlN. In the main body 21, the content of AlN as the main material is, for example, 50% by mass to 100% by mass, and this content is adjusted according to the desired material characteristics of the main body 21. For example, when high thermal conductivity is required for the main body 21, the content of AlN is preferably 80% by mass to 100% by mass.
[0028] The electrode 23 includes a conductor, and the conductor includes tungsten carbide (WC) and titanium nitride (TiN). In the present application, the description of "tungsten carbide" means a compound represented by the chemical formula "WC" and is a concept that does not include a compound represented by the chemical formula "W2C" described later. The total content of WC and TiN in the conductor is, for example, 90% by volume to 100% by volume. The total content of WC and TiN in the electrode 23 is, for example, 80% by volume to 100% by volume, and the inclusion of a different phase such as W2C is permitted as long as the content is such that the performance of the electrode 23 is not substantially affected. In this embodiment, the electrode 23 is substantially formed only of a conductor, and the conductor does not substantially include any substance other than WC and TiN. In other words, in this embodiment, the total content of WC and TiN in the conductor included in the electrode 23 is 100% by volume, and the total content of WC and TiN in the electrode 23 is also 100% by volume.
[0029] The content of TiN in the conductor contained in the electrode 23 is, for example, 5% by volume or more and 60% by volume or less, and is adjusted so that the difference in thermal expansion coefficient between the electrode 23 and the main body 21 approaches substantially 0. In the electrode 23, the intensity ratio of the main peaks of WC and TiN obtained by X-ray diffraction (XRD) (hereinafter also referred to as "WC-TiN peak ratio") is, for example, 0.80 or more and less than 1.0, and is adjusted so that the difference in thermal expansion coefficient between the electrode 23 and the main body 21 approaches substantially 0. The WC-TiN peak ratio is a value obtained by dividing the main peak intensity of WC by the sum of the main peak intensity of WC and the main peak intensity of TiN.
[0030] The thermal expansion coefficient (also referred to as the thermal expansion rate) of WC is lower than that of the main body 21 and that of AlN, which is the main material of the main body 21. The thermal expansion coefficient of TiN is higher than that of the main body 21 and that of AlN, which is the main material of the main body 21. The absolute value of the difference in the thermal expansion coefficient between the electrode 23 and the main body 21 (hereinafter also referred to as the "CTE difference") is, for example, 0.5 ppm / °C or less, and preferably 0.3 ppm / °C or less, in the range of 40°C or more and 1000°C or less. The lower limit of the CTE difference is not particularly limited, but is 0.0 ppm / °C or more. The resistivity of the electrode 23 at room temperature is, for example, 3.0×10 -5 Ω cm or less, preferably 2.5×10 -5 The resistivity is not particularly limited to a lower limit, but is, for example, 1.0×10 -5 Ω·cm or more.
[0031] As described later, the electrode 23 is a sintered body formed by firing together with the main body 21 or separately from the main body 21. The firing temperature is a high temperature of, for example, 1700°C or higher. The melting point of WC is 2870°C, and the melting point of TiN is 2930°C. The grain size of the sintered TiN is, for example, 0.7 μm or more and 1.0 μm or less, and preferably 0.7 μm or more and 0.9 μm or less. The grain size of the sintered TiN can be obtained by microstructural observation using a SEM (scanning electron microscope) or the like.
[0032] Next, an example of a manufacturing method for the main body 21 and electrode 23 (i.e., the compound sintered body 20) of the susceptor 1 will be described with reference to Fig. 2. In this example, a substantially disk-shaped portion in the lower half of the main body 21 (hereinafter referred to as the "first member") and a substantially disk-shaped portion in the upper half (hereinafter referred to as the "second member") are prepared, and the material for the electrode 23 is sandwiched between the first member and the second member and sintered, thereby manufacturing the main body 21 and the electrode 23.
[0033] Specifically, first, raw material powders of the main body 21 (i.e., the first and second members) are weighed out to have a predetermined composition, and the raw material powders are wet-mixed and then molded into a molded body of a predetermined shape by uniaxial pressing or the like (step S11). The molded body molded in step S11 is a precursor of the above-mentioned first and second members.
[0034] In step S11, for example, a commercially available high-purity fine powder is used as the AlN raw material. When the main body 21 contains MgO, for example, a commercially available high-purity fine powder is used as the MgO raw material. When the main body 21 contains MgAl2O4, for example, the above-mentioned commercially available MgO powder and commercially available high-purity fine powder of aluminum oxide (Al2O3) are heated and synthesized and used as the MgAl2O4 raw material. Alternatively, a commercially available high-purity fine powder of MgAl2O4 may be used as the MgAl2O4 raw material. The purity, average particle size, etc. of the AlN raw material, MgO raw material, and MgAl2O4 raw material are appropriately determined.
[0035] In step S11, the mixing conditions of the raw material powder (e.g., mixing time, type of solvent, etc.) are appropriately determined. As the solvent, for example, an organic solvent or ion-exchanged water can be used. In addition, in step S11, the raw material powder may be mixed by dry mixing.
[0036] In step S11, the molding conditions for the green body (e.g., the applied pressure, etc.) are appropriately determined. When the green body has a plate shape, the green body may be molded by filling the raw material powder into a hot press die or the like. The green body may be molded by various other methods as long as the shape can be maintained. For example, the slurry after wet mixing may be poured into a mold while still in a fluid state, and then the solvent component may be removed to form a green body of a predetermined shape.
[0037] Next, the two molded bodies (i.e., precursors of the first member and the second member) formed in step S11 are sintered by hot pressing or the like, and the obtained sintered bodies are processed into predetermined shapes to obtain the first member and the second member (step S12). The sintering conditions in step S12 (e.g., pressing pressure, sintering temperature, sintering time, etc.) are appropriately determined. The sintering of the molded bodies in step S12 may be performed by a method other than the hot pressing method.
[0038] Next, the raw material powder of the electrode 23 is weighed to have a predetermined composition, mixed, and kneaded with a solvent, a binder, and the like to produce an electrode paste, which is a precursor of the electrode 23 (step S13). In step S13, for example, commercially available high-purity fine powders of WC and TiN are used as the WC raw material and TiN raw material. The purity and average particle size of the WC raw material and TiN raw material are appropriately determined. The above-mentioned raw material powders are mixed, for example, by wet mixing. The mixing conditions of the raw material powders (for example, mixing time, type of solvent, etc.) are appropriately determined. For example, an organic solvent or ion-exchanged water can be used as the solvent. In step S13, the raw material powders may be mixed by dry mixing. In step S13, the types of the above-mentioned solvent (for example, organic solvent) and binder kneaded with the raw material powder are appropriately determined. In addition, step S13 may be performed before steps S11 and S12, or in parallel with steps S11 and S12.
[0039] The electrode paste produced in step S13 is applied in a predetermined shape to the upper surface of one of the sintered bodies (i.e., the first member) formed in step S12 by screen printing or the like. Then, after the electrode paste is dried in the atmosphere or the like for a predetermined time (e.g., 1 hour), a second member is laminated on the first member and the electrode paste to form a laminate (step S14).
[0040] In step S14, the application of the electrode paste may be performed by a method other than screen printing. In addition, in step S14, a molded body of the second member (i.e., the precursor molded in step S11) may be laminated on the first member and the electrode paste instead of the second member. Alternatively, a calcined body obtained by calcining a molded body of the second member may be laminated on the first member and the electrode paste instead of the second member. In addition, a molded body or a calcined body of the first member may be used instead of the first member which is a sintered body. In other words, the first member and the second member used in step S14 may be any of a sintered body, a calcined body, and a molded body.
[0041] Thereafter, the laminate formed in step S14 is fired by a hot press method or the like, so that the first member and the second member are integrated together to form the main body 21 and the electrode 23 (i.e., the compound sintered body 20) (step S15). The firing conditions in step S15 (e.g., the pressing pressure, firing temperature, firing time, etc.) are determined appropriately. The firing of the laminate in step S15 may be performed by a method other than the hot press method. Also, in the above-mentioned step S14, instead of the electrode paste, an electrode 23 formed by firing the electrode paste alone may be placed on the upper surface of the first member, and a compact, calcined body or sintered body of the second member may be laminated on the first member and the electrode 23.
[0042] Next, with reference to Tables 1 to 3, examples 1 to 16 of the compound sintered body 20 (i.e., the main body 21 and the electrode 23) according to the present invention and comparative examples 1 to 4 for comparison with the compound sintered body 20 will be described. In examples 1 to 16, the electrode 23 contains WC and TiN, whereas in comparative examples 1 to 4, the electrode 23 contains only one of WC and TiN.
[0043] [Table 1]
[0044] [Table 2]
[0045] [Table 3]
[0046] In Examples 1 to 16 and Comparative Examples 1 to 4, the main body 21 and the electrode 23 were manufactured by the above-mentioned steps S11 to S15. In Examples 1 to 16 and Comparative Examples 1 to 4, in step S11, a commercially available high-purity fine powder of AlN (oxygen content 0.8%, average particle size 1.3 μm) was used as the AlN raw material. In addition, a commercially available high-purity fine powder of MgO (purity 99% or more, average particle size 1.2 μm) was used as the MgO raw material. As the MgAl2O4 raw material, the above-mentioned commercially available MgO powder and a commercially available high-purity fine powder of aluminum oxide (Al2O3) (purity 99.99% or more, average particle size 0.5 μm) were mixed in a molar ratio of 1:1, heated and synthesized at 1300°C in an air atmosphere, and then pulverized to adjust the average particle size to 0.2 μm.
[0047] In Examples 1 to 16 and Comparative Examples 1 to 4, the wet mixing of the raw material powder in step S11 was performed by a ball mill using zirconia balls and a polypot. The mixing time was 20 hours, and the solvent used was an organic solvent. The slurry produced by the wet mixing was dried and then sieved to obtain the raw material powder for the main body 21. The molding of the compact in step S11 was performed by filling a die for uniaxial press molding with the raw material powder. The pressure during the uniaxial press molding was 100 kgf / cm. 2 The obtained compact was a substantially disk-like body having a diameter of 50 mm and a thickness of 10 mm. In Examples 1 to 16 and Comparative Examples 1 to 4, test specimens smaller than the actual compound sintered body 20 were prepared and used.
[0048] In Examples 1 to 16 and Comparative Examples 1 to 4, the sintering in step S12 was performed by hot pressing. Specifically, the above-mentioned molded body was placed in a graphite mold for hot pressing, and the molded body was set in a hot pressing furnace and sintered. The pressing pressure during sintering was 200 kgf / cm.2 The firing temperature (i.e., the maximum temperature during firing) was 1700°C or higher and 1780°C or lower. The firing time was 8 hours. The heating and cooling rates were 300°C / h. The firing atmosphere was evacuated when the temperature was raised to 1000°C, and nitrogen gas was then introduced. The gas pressure after the introduction of nitrogen gas was maintained at about 1.5 atm (about 0.152 MPa). When the temperature was lowered, the temperature control was stopped at 1400°C, and the furnace was cooled. The obtained sintered bodies (i.e., the first member and the second member) were each processed into an approximately circular plate shape with a diameter of 50 mm and a thickness of 5 mm.
[0049] In Examples 1 to 16 and Comparative Examples 1 to 4, in step S13, a commercially available high-purity fine powder of WC (purity of 99.9% or more, average particle size of 0.75 μm) and a commercially available high-purity fine powder of TiN (purity of 99% or more, average particle size of 0.6 μm) were used as the WC raw material and the TiN raw material.
[0050] In Examples 1 to 16, the wet mixing of the raw material powder in step S13 was performed by a ball mill using zirconia balls and a polypot. The mixing time was 20 hours, and the solvent used was an organic solvent. The slurry produced by the wet mixing was dried and then sieved to obtain the raw material powder of the electrode 23. In Comparative Examples 1 to 4, the above-mentioned WC raw material or TiN raw material was used as the raw material powder of the electrode 23. In Examples 1 to 16 and Comparative Examples 1 to 4, butyl carbitol and poly(n-butyl methacrylate) were used as the solvent and binder to be kneaded with the raw material powder when producing the electrode paste.
[0051] In Examples 1 to 16 and Comparative Examples 1 to 4, the application of the electrode paste in step S14 is performed by screen printing. The shape of the electrode paste applied to the first member is a substantially rectangular shape with a width of 5 mm and a length of 15 mm. The thickness of the electrode paste is 60 μm to 70 μm.
[0052] In Examples 1 to 16 and Comparative Examples 1 to 4, the sintering in step S15 was performed by hot pressing. Specifically, the above-mentioned molded body was placed in a graphite mold for hot pressing, and the molded body was set in a hot pressing furnace and sintered. The pressing pressure during sintering was 200 kgf / cm. 2 The firing temperature (i.e., the maximum temperature during firing) was 1700°C or higher and 1780°C or lower. The firing time was 8 hours. The heating and cooling rates were 300°C / h. The firing atmosphere was evacuated when the temperature was raised to 1000°C, and nitrogen gas was then introduced. The gas pressure after the introduction of nitrogen gas was maintained at approximately 1.5 atm (approximately 0.152 MPa). When the temperature was lowered, the temperature control was stopped at 1400°C, and the furnace was cooled.
[0053] In Tables 1 to 3, the thermal expansion coefficient of the base material (i.e., the main body 21) was measured in the range of 40°C to 1000°C by a method conforming to JIS-R1618 using a sintered sample cut out from the main body 21. The thermal expansion coefficient of WC was measured in the range of 40°C to 1000°C by a method conforming to JIS-R1618 using a bulk material prepared by hot-pressing the commercially available WC powder used in step S13 under the same conditions as in step S12. The thermal expansion coefficient of TiN was also measured in the same manner as WC. The thermal expansion coefficient of the electrode 23 was determined based on the thermal expansion coefficient of the above-mentioned WC alone and the thermal expansion coefficient of TiN alone, and the contents of WC and TiN in the electrode 23. Specifically, the thermal expansion coefficient of the electrode 23 was determined as the sum of the product of the thermal expansion coefficient of the WC alone and the WC content in the electrode 23, and the product of the thermal expansion coefficient of the TiN alone and the TiN content in the electrode 23. The CTE difference is the absolute value of the difference between the thermal expansion coefficient of the electrode 23 and the thermal expansion coefficient of the main body portion 21 described above.
[0054] The resistivity of the electrode 23 was determined as follows. First, a roughly rectangular parallelepiped test piece with a width, length and thickness of 9 mm was cut out from the compound sintered body 20 formed in step S15. The test piece was cut out so that an electrode 23 with a width of 5 mm and a length of 9 mm was embedded in the center. The electrode 23 with a width of 5 mm was exposed on both end faces of the test piece. The cross-sectional area S (cm 2) was obtained by measuring the width and length of electrode 23 at the end face of the test piece using an optical microscope. In addition, the distance between both end faces of the test piece where electrode 23 was exposed was measured using a vernier caliper, and was defined as the length L (cm) of electrode 23. The circuit for measuring resistance was constructed by applying conductive paste to both end faces of electrode 23 and connecting lead wires. Then, in the atmosphere at room temperature, a minute current I (mA) in the range of 0 mA to 150 mA was applied to electrode 23, and the minute voltage value V (mV) generated at that time was measured, and the resistance R (Ω) of electrode 23 was obtained by R = V / I. Then, the resistivity ρ (Ω·cm) of electrode 23 was obtained by ρ = R × S / L.
[0055] The composition of the electrode 23 was determined as follows. First, the upper half or the lower half of the test piece was removed to expose the upper or lower surface of the electrode 23, and the exposed electrode 23 was polished. Then, the crystalline phase was identified on the polished surface of the electrode 23 by an X-ray diffraction device (XRD). For the identification of the crystalline phase, a sealed tube type X-ray diffraction device (D8-ADVANCE manufactured by Bruker AXS Co., Ltd.) was used. The measurement conditions were CuKα, 40 kV, 40 mA, 2θ = 10 to 70°, and the measurement step width was 0.002°.
[0056] The WC-TiN peak ratio in electrode 23 is the intensity ratio of the main peaks of WC and TiN measured by the above-mentioned XRD. The WC-TiN peak ratio was calculated as I1 / (I1+I2), where I1 is the intensity of the (100) plane, which is the main peak of WC, and I2 is the intensity of the (200) plane, which is the main peak of TiN.
[0057] The grain size of sintered TiN in electrode 23 was obtained by observing the microstructure using SEM. Fig. 3 is an SEM image of electrode 23 of Example 6. Specifically, one surface of the test piece was polished to a mirror finish, and the polished surface of electrode 23 was observed using SEM. Then, an average diameter, which is the average of the major axis and minor axis of a predetermined number (e.g., several tens of particles), of sintered particles was calculated, and the arithmetic average of the average diameters of the predetermined number of sintered particles was determined as the grain size of sintered TiN.
[0058] In Example 1 and Comparative Examples 1-2, the first and second members of the main body 21 are formed by adding MgO to AlN. In Examples 2-16 and Comparative Examples 3-4, the first and second members of the main body 21 are formed by adding MgAl2O4 to AlN. In Examples 1-15 and Comparative Examples 1-4, the second member is the compact formed in step S11, and in Example 16, the second member is the sintered body formed in step S12. Note that the first member is the sintered body formed in step S12 in all Examples and Comparative Examples.
[0059] In all the examples, the electrode 23 contains WC and TiN. The electrode 23 may contain a small amount of W2C generated from WC, but the small amount of W2C does not substantially affect the performance of the electrode 23. In the comparative examples 1 and 3, the electrode 23 contains WC and does not contain TiN. In the comparative examples 2 and 4, the electrode 23 contains TiN and does not contain WC. In the examples 1 to 12 and 16 and the comparative examples 1 to 4, the electrode 23 is fired at a temperature of 1720°C. In the examples 13 to 15, the electrode 23 is fired at a temperature of 1700°C, 1740°C, and 1780°C, respectively.
[0060] In Examples 1, 3 to 4, the additive component in the main body 21 was changed to MgO and MgAl2O4, and the thermal expansion coefficient of the main body 21 was made closer. In Examples 2 to 6, the content of the additive component MgAl2O4 in the main body 21 was changed in the range of 5 mass% to 45 mass%, and the contents of WC and TiN in the electrode 23 were changed so that the CTE difference was 0.00 ppm / °C. In Examples 7 to 12, the content of the additive component MgAl2O4 in the main body 21 was fixed at 45 mass%, and the contents of WC and TiN in the electrode 23 were changed to change the CTE difference. In Examples 6, 13 to 15, the firing temperature was changed in the range of 1700°C to 1780°C. In Examples 6 and 16, the second member of the main body 21 in Example 6 was a molded body, and the second member of the main body 21 in Example 16 was a sintered body.
[0061] In Examples 1 to 16, the CTE difference, which is the absolute value of the difference in thermal expansion coefficient between electrode 23 and main body 21, was small at 0.00 ppm / °C to 0.50 ppm / °C, even though the thermal expansion coefficient of main body 21 changed due to the added components. On the other hand, in Comparative Examples 1 and 3 in which electrode 23 was made only of WC, the CTE difference was large at 0.60 ppm / °C to 1.80 ppm / °C. Also, in Comparative Examples 2 and 4 in which electrode 23 was made only of TiN, the CTE difference was large at 2.10 ppm / °C to 3.30 ppm / °C.
[0062] In Examples 1 to 16, the WC-TiN peak ratio in the electrode 23 was 0.80 to 0.99. In Comparative Examples 1 and 3 in which the electrode 23 was made of only WC, the WC-TiN peak ratio in the electrode 23 was 1.0, and in Comparative Examples 2 and 4 in which the electrode 23 was made of only TiN, the WC-TiN peak ratio in the electrode 23 was 0.0.
[0063] In Examples 1 to 16, the sintered grain size of TiN in electrode 23 was small, ranging from 0.74 μm to 0.96 μm. On the other hand, in Comparative Examples 2 and 4 in which electrode 23 was formed only from TiN, the sintered grain size of TiN in electrode 23 was large, ranging from 7.01 μm to 7.06 μm. In Comparative Examples 2 and 4, electrode 23 did not contain WC, which is believed to be the reason why abnormal grain growth of TiN occurred during sintering of electrode 23.
[0064] In Examples 1 to 16, the resistivity of the electrode 23 at room temperature was 2.0×10 -5 Ω cm~3.0×10 -5 In Comparative Examples 1 and 3 in which the electrode 23 was made of only WC, the resistivity of the electrode 23 at room temperature was 1.9×10 -5 Ω cm~2.0×10 -5 On the other hand, in Comparative Examples 2 and 4 in which the electrode 23 was formed only of TiN, the resistivity of the electrode 23 at room temperature was 5.1×10 -5 Ω cm~5.4×10 -5 It was large, Ω·cm.
[0065] As described above, the compound sintered body 20 includes a base material (i.e., the main body 21) mainly made of ceramic, and the electrode 23 disposed inside the main body 21. The electrode 23 includes WC and TiN. This makes it possible to reduce the difference in thermal expansion coefficient between the electrode 23 and the main body 21 while suppressing an increase in the resistivity of the electrode 23. As a result, damage such as cracks and breaks in the main body 21 caused by the difference in thermal expansion coefficient can be suppressed. Furthermore, when the electrode 23 is used as a resistance heating element, the amount of heat generated by the electrode 23 can be increased. When the electrode 23 is used as a chuck electrode, the chucking force with respect to the substrate 9 can be increased.
[0066] In the compound sintered body 20, the electrode 23 may be disposed on the surface of the main body portion 21. In other words, the electrode 23 is disposed inside or on the surface of the main body portion 21. Regardless of whether the electrode 23 is disposed inside or on the surface of the main body portion 21, in the compound sintered body 20, as described above, it is possible to reduce the difference in thermal expansion coefficient between the electrode 23 and the main body portion 21 while suppressing an increase in the resistivity of the electrode 23.
[0067] As described above, in the compound sintered body 20, the absolute value of the difference in thermal expansion coefficient between the electrode 23 and the main body 21 (i.e., the CTE difference) is preferably 0.3 ppm / °C or less in the range of 40°C or more and 1000°C or less. In this way, by suitably reducing the difference in thermal expansion coefficient between the electrode 23 and the main body 21, damage to the main body 21 caused by the difference in thermal expansion coefficient can be further suppressed.
[0068] As described above, the resistivity of the electrode 23 at room temperature is 3.0×10 -5 It is preferable that the resistivity of electrode 23 is Ω·cm or less. In this manner, by suitably reducing the resistivity of electrode 23, when electrode 23 is used as a resistance heating element, the amount of heat generated by electrode 23 can be further increased. Also, when electrode 23 is used as a chuck electrode, the chucking force with respect to substrate 9 can be further increased.
[0069] As described above, the content of TiN in the conductor contained in electrode 23 is preferably 5 volume % or more and 60 volume % or less. This makes it possible to suitably reduce the difference in thermal expansion coefficient between electrode 23 and main body 21 while suitably suppressing an increase in the resistivity of electrode 23, as in Examples 1 to 16 above.
[0070] As described above, in electrode 23, the intensity ratio of the main peaks of WC and TiN obtained by X-ray diffraction (i.e., the WC-TiN peak ratio) is preferably 0.80 or more and less than 1.0. This makes it possible to suitably reduce the difference in thermal expansion coefficient between electrode 23 and main body 21 while suitably suppressing an increase in the resistivity of electrode 23, as in Examples 1 to 16 above.
[0071] As described above, the total content of WC and TiN in the conductor contained in electrode 23 is preferably 100% by volume. This makes it possible to prevent an increase in manufacturing costs due to an increase in the number of types of conductor materials in electrode 23. More preferably, the total content of WC and TiN in electrode 23 is 100% by volume. This makes it possible to suppress an increase in the resistivity of electrode 23 compared to when electrode 23 contains a material other than the conductor (for example, the material of main body 21).
[0072] As described above, the sintered grain size of TiN in electrode 23 is preferably 0.7 μm or more and 1.0 μm or less. In this way, by suppressing abnormal grain growth of TiN, electrode 23 can be densified. As a result, an increase in the resistivity of electrode 23 can be suitably suppressed.
[0073] As described above, it is preferable that the main material of the main body 21 is AlN. This makes it possible to provide a highly versatile compound sintered body 20 that can be used in a variety of processes.
[0074] As described above, in the compound sintered body 20, the difference in thermal expansion coefficient between the electrode 23 and the main body 21 can be reduced while suppressing an increase in the resistivity of the electrode 23, and therefore the compound sintered body 20 is suitable for use as a semiconductor manufacturing equipment member in a semiconductor manufacturing device. The compound sintered body 20 is particularly suitable for use as a semiconductor manufacturing equipment member in a high-output semiconductor manufacturing device such as a high-power etching device. The susceptor 1 described above is a suitable example of a semiconductor manufacturing equipment member made using the compound sintered body 20. In the susceptor 1, the main body 21 is disk-shaped as described above, and a semiconductor substrate is placed on the main surface of the main body 21.
[0075] The manufacturing method of the above-mentioned compound sintered body 20 includes the steps of preparing the first member and the second member, which are a compact, a calcined body, or a sintered body mainly made of ceramic (steps S11 to S12), arranging the electrode 23 containing WC and TiN or a precursor of the electrode 23 on the first member, and then stacking the second member to form a laminate (step S14), and hot-press firing the laminate (step S15). As a result, as in the above, it is possible to reduce the difference in thermal expansion coefficient between the electrode 23 and the main body 21 while suppressing an increase in the resistivity of the electrode 23. As a result, it is possible to suppress damage such as cracks and breaks in the main body 21 caused by the difference in thermal expansion coefficient. In addition, when the electrode 23 is used as a resistance heating body, the amount of heat generated by the electrode 23 can be increased. When the electrode 23 is used as a chuck electrode, the chucking force with respect to the substrate 9 can be increased.
[0076] As described above, the absolute value of the difference in thermal expansion coefficient between electrode 23 and the first and second members after step S15 (i.e., CTE difference) is preferably 0.3 ppm / ° C. or less in the range of 40° C. to 1000° C. In this manner, by suitably reducing the difference in thermal expansion coefficient between electrode 23 and the first and second members, damage to the first and second members (i.e., main body 21) caused by the difference in thermal expansion coefficient can be further suppressed.
[0077] As described above, the sintering temperature in step S15 is preferably not less than 1700° C. and not more than 1780° C. In the compound sintered body 20, even when sintered at such a high temperature, abnormal grain growth of TiN can be suppressed and the densification of the electrode 23 can be improved.
[0078] The above-described compound sintered body 20 and the method for manufacturing the compound sintered body 20 can be modified in various ways.
[0079] For example, the content of TiN in the conductor contained in the electrode 23 may be less than 5 volume % or more than 60 volume %.
[0080] In the electrode 23, the intensity ratio of the main peaks of WC and TiN obtained by X-ray diffraction (ie, the WC-TiN peak ratio) may be less than 0.80.
[0081] The sintered grain size of the TiN in the electrode 23 may be less than 0.7 μm and may be greater than 1.0 μm.
[0082] The resistivity of the electrode 23 at room temperature is 3.0×10 -5 It may be greater than Ω·cm.
[0083] The absolute value of the difference in thermal expansion coefficient between electrode 23 and main body portion 21 (ie, the CTE difference) may be greater than 0.3 ppm / °C in the range of 40°C or more and 1000°C or less.
[0084] The main material of the main body 21 may be a ceramic other than AlN.
[0085] The conductor of electrode 23 may contain a material other than WC and TiN. In other words, the total content of WC and TiN in the conductor may be less than 100% by volume. Furthermore, electrode 23 may contain a material other than a conductor (for example, a ceramic such as AlN, which is the main material of main body 21). In other words, the content of the conductor in electrode 23 may be less than 100% by volume.
[0086] In the method for producing the compound sintered body 20, the firing temperature in step S15 may be lower than 1700°C or may be 1780°C or higher.
[0087] In the susceptor 1, the electrode 23 may be an RF electrode for plasma processing.
[0088] The compound sintered body 20 may be used to manufacture other semiconductor manufacturing equipment components (e.g., rings, shower heads, etc.) that are provided in the semiconductor manufacturing equipment other than the susceptor 1. Furthermore, the compound sintered body 20 may be used to manufacture components used in equipment other than the semiconductor manufacturing equipment. For example, the compound sintered body 20 may be used to manufacture a susceptor that supports a substrate other than a semiconductor substrate, or may be used to manufacture a ceramic heater that heats an object.
[0089] The configurations in the above-described embodiment and each of the modified examples may be combined as appropriate as long as they are not mutually inconsistent. [Industrial Applicability]
[0090] INDUSTRIAL APPLICABILITY The present invention is applicable to the field of semiconductor manufacturing equipment, for example, in the manufacture of susceptors that hold and heat semiconductor substrates. [Explanation of symbols]
[0091] 9 Substrate 20. Composite sintered body 21 Main body 23 electrodes S11~S15 steps
Claims
1. A compound sintered body, a disk-shaped base material containing 5% by mass to 45% by mass of magnesium aluminum spinel and the remainder being aluminum nitride, the base material having a main surface on which a semiconductor substrate is placed; An electrode disposed within or on the surface of the substrate; Equipped with The electrode is Tungsten carbide, Titanium nitride, A composite sintered body comprising:
2. The composite sintered body according to claim 1, A composite sintered body, wherein the total content of the tungsten carbide and the titanium nitride in the conductor contained in the electrode is 100 volume %.
3. A compound sintered body, A disk-shaped base material containing 50% by mass to 100% by mass of aluminum nitride and having a main surface on which a semiconductor substrate is placed; An electrode disposed within or on the surface of the substrate; Equipped with The electrode is Tungsten carbide, Titanium nitride, Including, A composite sintered body, wherein the total content of the tungsten carbide and the titanium nitride in the conductor contained in the electrode is 100 volume %.
4. The composite sintered body according to claim 2 or 3, A composite sintered body, wherein the total content of the tungsten carbide and the titanium nitride in the electrode is 100 volume %.
5. 5. The composite sintered body according to claim 1, The resistivity of the electrode at room temperature is 3.0×10 -5 A composite sintered body having a resistivity of Ω·cm or less.
6. 6. The composite sintered body according to claim 1, A compound sintered body, wherein the content of said titanium nitride in the conductor contained in said electrode is 5 volume % or more and 60 volume % or less.
7. 7. The composite sintered body according to claim 1, A composite sintered body, characterized in that in the electrode, the intensity ratio of the main peaks of the tungsten carbide and the titanium nitride obtained by X-ray diffraction method is 0.80 or more and less than 1.
0.
8. 8. The composite sintered body according to claim 1, A compound sintered body, characterized in that the sintered grain size of the titanium nitride in the electrode is 0.7 μm or more and 1.0 μm or less.
9. A method for producing a compound sintered body comprising a disk-shaped base material having a semiconductor substrate placed on a main surface thereof and an electrode disposed inside the base material, the method comprising the steps of: a) preparing a first member and a second member which are a green body, a calcined body or a sintered body mainly made of ceramic; b) disposing an electrode containing tungsten carbide and titanium nitride or a precursor of the electrode on the first member, and then laminating the second member to form a laminate; c) hot press sintering the laminate; Equipped with The method for producing a composite sintered body, wherein the first member and the second member after completion of the step c) contain 5% by mass to 45% by mass of magnesium aluminum spinel and the remainder is aluminum nitride.
10. A method for producing a compound sintered body comprising a disk-shaped base material having a semiconductor substrate placed on a main surface thereof and an electrode disposed inside the base material, the method comprising the steps of: a) preparing a first member and a second member which are a green body, a calcined body or a sintered body mainly made of ceramic; b) disposing an electrode containing tungsten carbide and titanium nitride or a precursor of the electrode on the first member, and then laminating the second member to form a laminate; c) hot press sintering the laminate; Equipped with the first member and the second member after completion of the step c) contain 50 mass % to 100 mass % aluminum nitride; A method for producing a composite sintered body, characterized in that after completion of the step c), a total content of the tungsten carbide and the titanium nitride in the conductor contained in the electrode is 100 volume %.
11. A method for producing the compound sintered body according to claim 9 or 10, A method for producing a compound sintered body, wherein the sintering temperature in the step c) is 1700°C or higher and 1780°C or lower.
Citation Information
Patent Citations
Wafer holder
JP1996236599A
Electrostatic chuck
JP1998229117A
Electrostatic chuck
JP2007173592A
Ceramic structure, manufacturing method of the same, and member for semiconductor manufacturing apparatus
JP2017157328A
Complex sintered body, semiconductor manufacturing apparatus and manufacturing method of complex sintered body
JP2019167288A